Confirmed and Potential Roles of Bacterial T6SSs in the Intestinal Ecosystem - Chen, Can; Yang, Xiaobing; Shen, Xihui (Frontiers in Microbiology, 2019)
The contact-dependent type VI secretion system (T6SS) in diverse microbes plays crucial roles in both inter-bacterial and bacteria-host interactions. As numerous microorganisms inhabit the intestinal ecosystem at a high density, it is necessary to consider the functions of T6SS in intestinal bacteria. In this mini-review, we discuss T6SS-dependent functions in intestinal microbes, including commensal microbes and enteric pathogens, and list experimentally verified species of intestinal bacteria containing T6SS clusters. Several seminal studies have shown that T6SS plays crucial antibacterial roles in colonization resistance, niche occupancy, activation of host innate immune responses, and modulation of host intestinal mechanics. Some potential roles of T6SS in the intestinal ecosystem, such as targeting of single cell eukaryotic competitors, competition for micronutrients, and stress resistance are also discussed. Considering the distinct activities of T6SS in diverse bacteria residing in the intestine, we suggest that T6SS research in intestinal microbes may be beneficial for the future development of new medicines and clinical treatments.